Performance trends matter: But why, how, and when? - REB, Jochen (Institutional Knowledge at Singapore Management University, 2018)
That performance is dynamic and varies over time has long been recognized. However, research is only beginning to understand the implications of dynamic performance for performance appraisals and performance-based decisions. Against this backdrop, despite what we see as serious methodological concerns (e.g., single-item measures, operationalization of variables), we believe that Schmidt (2017) makes several contributions that point to important directions for future research.